THE USE OF CONSONANT ELISION BY SRI MULYANI DURING HER INTERVIEW SESSION WITH THE BANKER - Anggi Rizky Firdhani; Lia Maulia Indrayani; Sutiono Mahdi (STKIP Siliwangi, 2018)
This research is entitled “The Use of Consonant Elision by Sri Mulyani During Her Interview Session with The Banker”. The objects of this research are the consonant elisions that are produced by Sri Mulyani when she was interviewed by The Banker. The objectives of this research are to describe and analyze the frequency of consonant elision used by Sri Mulyani and to find out the phonemes that are often being elision-ed by Sri Mulyani in her interview with The Banker. The analysis of this research was done by using descriptive qualitative analysis method. This study uses Carr’s (2008), Giegerich’s (1992), and Roach’s (2001) theories about phonological rules and elision. This study shows that during her interview, Sri Mulyani uses consonant elision for 26 times and she tends to do the omission to the phoneme /t/ (19 times), /d/ (5 times), /r/ (1 times), and /s/ (1 times).